2021
DOI: 10.1002/er.6359
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the performance of concentrator photovoltaic/thermoelectric generator system integrated with a new 3D printed microchannel heat sink

Abstract: Finding the most optimal configuration of hybrid concentrator photovoltaic (CPV)-thermoelectric power generator (TEG) system integrated with a microchannel heat sink (MCHS) is of great importance to achieve the best performance. Thus, two different hybrid configurations were chosen for the study including CPV/TEG/heat sink and CPV/heat sink/TEG. In addition, the performance of both hybrid configurations was compared with standalone CPV/heat sink and TEG/heat sink. In the conventional hybrid design, the TEG was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…The model was validated with the experimental work of Rezania et al [77] and could even predict a positive net output power under optimal conditions. Abdo et al [81] used a 3D printed microchannel heat exchanger to cool a combination of photovoltaic (PV) cell and TEG. It was printed by laser sintering of maraging steel with a thermal heat conductivity of 11.4 W•m −1 •K −1 .…”
Section: Microchannel and Minichannelmentioning
confidence: 99%
“…The model was validated with the experimental work of Rezania et al [77] and could even predict a positive net output power under optimal conditions. Abdo et al [81] used a 3D printed microchannel heat exchanger to cool a combination of photovoltaic (PV) cell and TEG. It was printed by laser sintering of maraging steel with a thermal heat conductivity of 11.4 W•m −1 •K −1 .…”
Section: Microchannel and Minichannelmentioning
confidence: 99%
“…The experimental results indicated that although there were no hot spots arising on the ceramic heat sink, the optimizations of channels on their size, compactness, or configuration were necessary for more uniform cooling. For instance, the manifold microchannel heat sinks have been designed and verified to be more efficient for uniform cooling, 17,18 which inspired us to optimize the ceramic-based heat sink in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Abdo et al 29 presented an experimental research on the thermal control of a CPV/thermoelectric generator (TEG) system placed or added with a brand-new microchannel heat sink. The researchers have designed two arrangements for the study, that is, a conventional system (CPV/TEG/heat sink) and a new (CPV/heat sink/TEG) system.…”
mentioning
confidence: 99%